Accounting and the government of the agricultural economy: Arrigo Serpieri and the Reclamation Consortia. (1st September 2016) - Sargiacomo, Massimo; Ianni, Luca; D'Andreamatteo, Antonio; D'Amico, Luciano
ABSTRACT: Drawing on primary sources gathered from repositories in Abruzzo, Bologna and Rome, this study – underpinned by the framework of governmentality – analyses the accounting, financial and governmental practices deployed as a consequence of the Reclamation Consortia in Fascist Italy. In a scenario stimulated by the ascent of the Fascist discourse on the Agricultural Corporative Economy, this analysis seeks to show the new technologies of government deployed by the State and local communities through the Reclamation Consortia Reform. The study also unveils the leading role in the change process played by Arrigo Serpieri who, besides acting as Under Secretary of State at the Ministry of Agriculture in Mussolini's government, was considered at the time Italy's most important agricultural expert.